Optimization of Delivery Cost on Reverse Logistic for Product Claim in the Two-Wheel Vehicle Industry - Paduloh, Paduloh; Mayana, Tiswy (Jurnal Ilmiah Teknik Industri, 2023)
Product returns are one of the obstacles faced by two-wheeled motor vehicle industry companies in Indonesia, where the company's head office is based in Japan. The obstacle faced is the excess cost of shipping product claims compared to the planned cost budget. These products are replacement parts for CBU (completely built-up) units for two-wheeled motor vehicles exported to Japan. This case will be solved using reverse logistics, where the initial analysis is carried out by finding the value of the bullwhip effect on the company's orders and requests. The next stage is forecasting for the next period using the ARIMA method using Rstudio. The results showed the occurrence of a bullwhip effect, and then the best result was the ARIMA model (0,1,3) (2,1,0). The value of the bullwhip effect managed to decrease by applying the forecasting model. Then optimizing the shipping cost of claim products processed by LINGO results in a 5% reduction in shipping costs from the budget.